2007
DOI: 10.1590/s0034-70942007000100008
|View full text |Cite
|
Sign up to set email alerts
|

Influência da procainamida sobre o bloqueio neuromuscular produzido pelo rocurônio e investigação sobre o mecanismo de ação da procainamida na junção neuromuscular

Abstract: JUSTIFICATIVA E OBJETIVOS:A potencialização da procainamida sobre o bloqueio neuromuscular produzido pela d-tubocurarina já está comprovada, porém o mecanismo é controverso. O objetivo do estudo foi avaliar a influência da procainamida no bloqueio neuromuscular produzido pelo rocurônio e investigar os mecanismos desta interação. MÉTODO: Foram utilizados 15 ratos (250 a 300 g) em preparação descrita por Bülbring. Formaram-se os seguintes grupos (n = 5 cada): procainamida -20 µg.mL -1 (Grupo I); rocurônio -4 µg.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…Besides the likeness to the receivers, this stereoisomerism is also factor that contributes to the cellular membranes fluidly 19 . The results of this study resemble each other to the experimental and clinical researches [2][3][7][8][9][11][12][16][17] that also demonstrated that local anesthetics employed separately for different routes, don't commit neuromuscular transmission, but they potentiate neuromuscular blockade produced for different neuromuscular blocking.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Besides the likeness to the receivers, this stereoisomerism is also factor that contributes to the cellular membranes fluidly 19 . The results of this study resemble each other to the experimental and clinical researches [2][3][7][8][9][11][12][16][17] that also demonstrated that local anesthetics employed separately for different routes, don't commit neuromuscular transmission, but they potentiate neuromuscular blockade produced for different neuromuscular blocking.…”
Section: Discussionsupporting
confidence: 81%
“…Clinical assays describe that local anesthetics by peridural route, routine used in association to general anesthesia, can interact and potentiate the effects of neuromuscular blocking agents [2][3]7,12 , interaction also observed in experimental studies 9,11 . However, although these effects have been experimentally demonstrated in isolated preparations and clinical assays, the influence in neuromuscular transmission and in neuromuscular blockade produced by competitive neuromuscular blocking agents it is still objective of little investigation 1-3, 6-9,11-12,14 .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The influence of local anaesthetics on these parameters may indicate a presynaptic action, consequently decreasing acetylcholine release or reducing the sensitivity of the postjunctional membrane to acetylcholine. [ 1 3 9 10 11 12 13 ] In our study, impaired neurotransmitter release was observed. This event was demonstrated by a progressive decrease in the frequency and amplitude of MEPPs.…”
Section: Discussionsupporting
confidence: 50%
“…Through postsynaptic action, binding to different specific acetylcholine sites may block acetylcholine-induced contractile response, temporarily occluding nicotinic receptor channels. [ 8 13 14 15 16 17 18 19 ]…”
Section: Discussionmentioning
confidence: 99%